2018
DOI: 10.1038/s42005-018-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Spin-wave interference in magnetic vortex stacks

Abstract: Spin waves with wavelengths in the nanometre range could serve as data carriers in future magnonic logic or signal processing devices. We investigate the interference of spin waves emitted from magnetic vortices in two exchange-coupled vortex stacks. The spin-wave dynamics are studied using scanning transmission X-ray microscopy and micromagnetic simulations. Stacks of vortices provide an excellent controllability of spin-wave properties including a tunable wavelength in the 100 nm regime and manipulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It has been shown that local magnetic formations such as domain walls [45][46][47], edge bound demagnetizing fields [33,48,49], or vortices [23,24,50] can function as spin wave emitters offering effective "antenna" widths well below 200 nm. A major advantage of this approach is that the devices providing such formations are a lot larger than these effective widths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that local magnetic formations such as domain walls [45][46][47], edge bound demagnetizing fields [33,48,49], or vortices [23,24,50] can function as spin wave emitters offering effective "antenna" widths well below 200 nm. A major advantage of this approach is that the devices providing such formations are a lot larger than these effective widths.…”
Section: Resultsmentioning
confidence: 99%
“…Refs. [23,24,50]). As this measurement, again, combines signals from the YIG and the Permalloy, to make sure that the radial waves and the implied vortex are indeed in the YIG film, a second measurement at the same frequency was conducted at the L 3 edge of nickel.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nanoscale spin textures in magnetic materials have gained attention for their potential as functional elements in spin‐wave devices. In particular, spin‐wave guiding, generation, and tunable transmission were observed at naturally occurring spin textures such as vortices and domain walls.…”
mentioning
confidence: 99%
“…When two ferromagnetic disks are overlapped, spin waves emitted from the vortex cores can generate interference patterns as studied by Behncke and coworkers [425]. The static magnetic state is shown in the bottom panel of Fig.…”
Section: Short-wavelength Spin Waves In Magnetic Vorticesmentioning
confidence: 86%